Semaphorin4A Is Cytotoxic to Oligodendrocytes and Is Elevated in Microglia and Multiple Sclerosis. (25th May 2015) - Leitner, Dominique F.; Todorich, Bozho; Zhang, Xuesheng; Connor, James R.
We have previously established that T cell immunoglobulin and mucin domain containing 2 (Tim2) is an H-ferritin receptor on oligodendrocytes (OLs). Tim2 also binds Semaphorin4A (Sema4A). Sema4A is expressed by lymphocytes, and its role in immune activation is known; however, its relationship to diseases that are known to have myelin damage has not been studied. In this study, we demonstrate that Sema4A is cytotoxic to OLs in culture: an effect accompanied by process collapse, membrane blebbing, and phosphatidylserine inversion. We further demonstrate that Sema4A preferentially binds to primary OLs but not astrocytes: an observation consistent with the lack of expression of Tim2 on astrocytes. We found that Sema4A protein levels are increased within multiple sclerosis plaques compared with normal-appearing white matter and that Sema4A induces lactate dehydrogenase release in a human OL cell line. The chief cellular source of Sema4A within the multiple sclerosis plaques appears to be infiltrating lymphocytes and microglia. Macrophages are known to express Sema4A, so we interrogated microglia as a potential source of Sema4A in the brain. We found that rat primary microglia express Sema4A which increased after lipopolysaccharide activation. Because activated microglia accumulate iron, we determined whether iron status influenced Sema4A and found that iron chelation decreased Sema4A and iron loading increased Sema4A in activated microglia. Overall, our data implicate Sema4A in the destruction of OLs and reveal that its expression is sensitive to iron levels.